The devil may dance eaudiobook A novel. - Tapper, Jake (Charlie and Margaret Marder Mysteries., 2021)
Charlie and Margaret discover the dark side of Hollywood in this sequel to New York Times bestseller The Hellfire Club— a thrilling cocktail of corruption and ambition from CNN's Jake Tapper. Charlie and Margaret Marder, political stars in 1960s Washington DC, know all too well how the tangled web of power in the nation's capital can operate. But while they long to settle into the comforts of home, Attorney General Robert Kennedy has other plans. He needs them to look into a potential threat not only to the presidency, but to the security of the United States itself. Charlie and Margaret quickly find themselves on a flight to sunny Los Angeles, where they'll face off against a dazzling world of stars and studios. At the center of their investigation is Frank Sinatra, a close friend of President John F. Kennedy and a rumored mob crony, whom Charlie and Margaret must befriend to get the inside scoop. But in a town built on illusions, where friends and foes all look alike, nothing is easy, and drinks by the pool at the Sands and late-night adventures with the Rat Pack soon lead to a body in the trunk of their car. Before they know it, Charlie and Margaret are being pursued by sinister forces from Hollywood's stages to the newly founded Church of Scientology, facing off against the darkest and most secret side of Hollywood's power. As the Academy Awards loom, and someone near and dear to Margaret goes missing, Charlie and Margaret find the clock is not only ticking but running out. Someone out there knows what they've uncovered and can't let them leave alive. Corruption and ambition form a deadly mix in this fast-paced sequel to The Hellfire Club .